Лазерно-стимульоване збiльшення вiдбиваючої здатностi монокристалiчного n-GaAs(100) - Gentsar, P. O.; Vlasenko, O. I.; Levytskyi, S. M. (Publishing house "Academperiodika", 2018)
The results of optical researches concerning the reflection spectra of n-GaAs(100) single crystals with a specific resistance of 10 Ωcm (at room temperature) measured in a light wave-length interval of 0.2–1.7 мm before and after the laser irradiation to an energy dose of 66–108 mJ/cm2 are reported. The experiment revealed a growth in the reflectance of the examined crystals after their laser treatment. This integral effect is explained as a result of the difference between the optical characteristics (the complex refractive index) in the near-surface layer and in the bulk of the irradiated material.